2021
DOI: 10.1016/s0140-6736(21)01497-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pain control among patients with cancer in hospitals of the Gaza Strip: a cross-sectional study

Abstract: Background Poor control of cancer pain is a major public health problem worldwide. Many potential barriers can lead to suboptimal treatment of cancer pain. One such barrier is inadequate measurement and assessment of cancerrelated pain control. This study aimed to assess current pain control and management for hospitalized adult patients with cancer in the Gaza Strip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…All patients were followed up 1 month after the operation, and the questionnaire survey was used to quantitatively evaluate the recovery of the donor site in terms of appearance, sensory, and movement. Also, oral functions, including eating and pronunciation, were assessed on a scale of 5 levels, which contains great satisfaction, satisfaction, average, dissatisfaction, and disappointment, using the Likert scoring system 6 . The higher the score is, the more satisfied they are.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were followed up 1 month after the operation, and the questionnaire survey was used to quantitatively evaluate the recovery of the donor site in terms of appearance, sensory, and movement. Also, oral functions, including eating and pronunciation, were assessed on a scale of 5 levels, which contains great satisfaction, satisfaction, average, dissatisfaction, and disappointment, using the Likert scoring system 6 . The higher the score is, the more satisfied they are.…”
Section: Methodsmentioning
confidence: 99%
“…Also, oral functions, including eating and pronunciation, were assessed on a scale of 5 levels, which contains great satisfaction, satisfaction, average, dissatisfaction, and disappointment, using the Likert scoring system. 6 The higher the score is, the more satisfied they are.…”
Section: Postoperative Evaluationmentioning
confidence: 99%
“…Several studies have evaluated the general mental health status and propensity of depression in Palestine and found that the general population has a relatively higher propensity for depression than that reported in other countries. One study in Gaza City conducted at the Islamic University of Gaza (IUG) and Al-Quds University (Azhar Branch (Q-AZ) Medical Schools), reported that the general population had 29.3% moderate depression, 15.2% severe depression, and 28.4% extreme depressive symptoms according to the DASS 21 questionnaire (57). A second study reported 37.2% of university students in the Gaza Strip suffered from moderate depression and 3.1% suffered from severe depression, measured using a socioeconomic questionnaire prepared by the researcher, the Siege Checklist by the Gaza Community Mental Health Program, the Taylor Manifestation Anxiety Scale (TMAS), and the Beck Depression Inventory (BDI-2) (56).…”
Section: Introductionmentioning
confidence: 99%